Community peer training for people with spinal cord injury in Iceland: A Pilot study - Hrafnhildur Hanna Þrastardóttir 1995- (2020)
Introduction: This thesis is the first study on the inaugural peer-based Active Rehabilitation (AR) training program for community dwelling individuals with spinal cord injury (SCI) in Iceland. Objectives: (1) To pilot the implementation of the evaluation of the inaugural AR program in Iceland; (2) to explore the participants’ experiences with the program and with the implementation of the program evaluation; (3) report preliminary findings about the effects of the program on physical independence, wheelchair skills, resilience, and quality of life, and (4) report qualities and characteristics of peer mentors involved in the program. Design: A pilot prospective cohort study design combined with a qualitative exploration through semi- structured interviews. Methods: All three program participants with SCI completed a survey that comprised a battery of outcome measures at the beginning and at the end of the program, and at three months follow-up. Participants also completed a practical wheelchair test at the beginning and at the end of the program. Qualitative data regarding participants’ views on the program and on the research process were collected through an interview at three months follow-up. All four peer mentors with SCI completed a survey and a practical wheelchair test at one occasion during the program. Results: Two themes were identified about the participants’ experiences and perceptions of the study and the AR program: 1) Program evaluation facilitates participants ́ progress, and 2) stimulating learning environment. At an individual level, participants showed improvements in wheelchair skills, assessed through wheelchair skills questionnaire and the Queensland Evaluation of Wheelchair Skills on completion of the program compared to baseline. Also, individuals reported improvements on resilience and satisfaction with physical health at 3 months follow-up compared to baseline. No apparent changes could be seen on the Spinal Cord Independence Measure Self-Report. The peer mentors scored higher than the ...